Metabolic parameters of postmenopausal women after quinoa or corn flakes intake - a prospective and double-blind study - De Carvalho, Flavia Giolo [UNESP]; Ovidio, Paula Payao; Padovan, Gilberto Joao; Jordao Junior, Alceu Afonso; Marchini, Julio Sergio; Navarro, Anderson Marliere (Informa Healthcare, 2014)
A prospective and double-blind study was conducted on 35 women with weight excess who consumed 25 grams of quinoa flakes (QF) or corn flakes (CF) daily during a period of four consecutive weeks. At the beginning (T1) and at the end (T2) of the intervention, total calorie intake was evaluated, anthropometric assessment was performed, blood was collected for the determination of glucose, total cholesterol and fractions, oxidative stress markers, vitamin E and enterolignans. Significant reductions were detected in serum triglyceride (CF group = 133.9 +/- 89.4 to 113.7 +/- 57 mg/dl and QF group = 112.3 +/- 35 to 107.9 +/- 33.1 mg/dl), TBARS (CF group = 3.2 +/- 0.8 to 2.9 +/- 0.5 mu mol/l and QF group = 3.06 +/- 0.6 to 2.89 +/- 0.5 mu mol/l) and vitamin E concentrations (CF group = 19.5 +/- 5 to 17.9 +/- 4 mu M and QF group = 17.9 +/- 4 to 16.9 +/- 3 mu M) and an increase in urinary excretion of enterolignans (CF group = 2.05 +/- 1.3 to 2.24 +/- 1.4 nm/ml and QF group = 2.9 +/- 1.6 to 3.2 +/- 2.7 nm/l), in both study groups. The reduction of total cholesterol (191 +/- 35 to 181 +/- 28 mg/dl) and LDL-cholesterol (LDL-c) (129 +/- 35 to 121 +/- 26 mg/dl), and the increase in GSH (1.78 +/- 0.4 to 1.91 +/- 0.4 mu mol/l) occurred only in the QF group, showing a possible beneficial effect of QF intake.
Keywords: Cholesterolemia; corn flakes; oxidative stress; postmenopause; quinoa